PERANAN TATA LETAK OBJEK PAMERAN, TATA WARNA DAN PENCAHAYAAN DALAM MENARIK MINAT PENGUNJUNG MUSEUM MACAN JAKARTA - Rifai, Diva Meiliana; Widiyanti (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
According to the International Council of Museums (ICOM): in the Indonesian Museum Guidelines, 2008.museum is an institution that is permanent, not seeking profit, serving society and its development, open to thepublic, acquiring, maintaining, relating and displaying artifacts concerning human identity and theirenvironment for the purposes of study, education and recreation. Tourist interest in visiting museums isminimal because heritage tourism in Indonesia is not popular enough, as a sign that there is a lack of museumfacilities to attract visitors. As a solution, this can be overcome by arranging the interior design of the museumaccording to current trends or styles, in addition to fulfilling The main function of the museum itself is to showthe stored collection values to the public. The museum can also be used as a selfie spot so that it can attract theinterest of visitors who come.The research object to be discussed is The Museum of Modern and Contemporary Art in Nusantara or MuseumMACAN. The purpose of this research is to find out the causes of low public interest in visiting museums. Themethodology used in this study is a combination of 2 methods, namely descriptive and quantitative analysis.Descriptive analysis will be used on research variables regarding object layout and also color layout.Quantitative analysis will be used on research variables regarding lighting.Keywords: register up to 6keywords here